GEOCHRONOLOGY (U-Pb) AND ISOTOPE GEOCHEMISTRY (Sr/Sr AND Pb/Pb) APPLIED TO THE VARZEA DO CAPIVARITA METAMORPHIC SUITE, DOM FELICIANO BELT, SOUTHERN BRAZIL: INSIGHTS AND PALEOGEOGRAPHICAL IMPLICATIONS TO WEST GONDWANA EVOLUTION - Gruber, Leonardo; Porcher, Carla Cristine; Geller, Humberto; Fernandes, Luís Alberto D’Ávilla; Koester, Edinei (Geochimica Brasiliensis, 2016)
Geochronological and isotope geochemistry analysis on the marbles and pelitic gneisses outcropping in the Várzea do Capivarita Metamorphic Suite in the Dom Feliciano Belt (DFB), southern Brazil, confirms its origin during the agglutination of Congo-Kalahari-La Plata cratons into the Gondwana Supercontinent, in the Tonian-Cryogenian periods. Detrital ages displayed provenance from local sources (2.2 - 2.0 Ga), from development of rifting processes (1.7 Ga) to agglutination of terrains in the Neoproterozoic (0.7 Ga), and constraints the sediments deposition within minimum detrital age of 714.3 ± 3.9 Ma and metamorphic age of 618 ± 7.3 Ma. 206Pb/204Pb and 207Pb/204Pb analysis displayed variations from ratios near those obtained to stromatolitic dolomites in Gariep Belt (Kalahari) and some o of the less radiogenic ratio are similar to signatures of Neoproterozoic (ca. 800 Ma) volcanic arcs (Cerro Bori Continental Arc) in the Rio de La Plata craton. Comparison with others marble-schists sequences from DFB, Marmora Terrane and African sequences lead to the interpretation of these sediments representing small-area basins developing along little shallow bays in the agglutination of terrains between Kalahari and La Plata cratons in the Neoproterozoic. 87Sr/86Sr ratio of 0.70609 found in marbles could also be considered a West Gondwana extension of the Sturtian glacial epoch.